Malaria control and elimination - Ariey, Frédéric; Gay, Frédérick; Ménard, Robert (Methods in molecular biology, 2019)
Country-Owned, Country-Driven: Perspectives from the World Health Organization on Malaria Elimination -- Current Situation of Malaria in Africa -- Current Malaria Situation in Asia-Oceania -- Malaria Situation in Latin America and the Caribbean: Residual and Resurgent Transmission and Challenges for Control and Elimination -- Diagnosing Malaria: Methods, Tools, and Field Applicability -- Serological Profiling for Malaria Surveillance Using a Standard ELISA Protocol -- Controlled Human Malaria Infection (CHMI) Studies: Over 100 Years of Experience with Parasite Injections -- In Vivo Assessments to Detect Antimalarial Resistance -- Plasmodium falciparum In Vitro Drug Resistance Selections and Gene Editing -- An Update on Artemisinin Resistance -- Antimalarial Drugs for Malaria Elimination -- Vaccine Development: From Preclinical Studies to Phase 1/2 Clinical Trials -- The Advanced Development Pathway of the RTS,S/AS01 Vaccine -- Live Vaccines against Plasmodium Pre-Erythrocytic Stages -- Development of Blood Stage Malaria Vaccines -- Insecticide-Treated Mosquito Nets -- Sampling Adult Populations of Anopheles Mosquitoes -- Insecticides and Insecticide Resistance -- Herbal Remedies to Treat Malaria in Madagascar: Hype and Hope -- Vade Retro Malaria: The Vagaries of Eradication Campaigns